2022
DOI: 10.3390/life13010109
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Analgesic Properties of Chemically Characterized Polyphenol-Rich Extract from Withania adpressa Coss. ex Batt

Abstract: The current work was undertaken to investigate the chemical composition, antioxidant, anti-inflammatory, and analgesic properties of a polyphenol-rich fraction from Withania adpressa Coss. ex Batt. After being extracted, the polyphenol-rich fraction was chemically characterized through use of high-performance liquid chromatography (HPLC). Antioxidant potency was assessed through the use of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and total antioxidant capacity (TAC). Inflammatory and analgesic properties were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, the diferent organs of the plant under study were tested as potential natural antioxidants, where the highest activity was observed in leaf extracts with IC 50 � 0.166 ± 0.001 mg/mL compared to the stems, fruits, and roots with the following values, 0.076 ± 0.001 mg/mL, 0.772 ± 0.043 mg/ml, and 0.370 ± 0.002 mg/mL, respectively [45]. Based on the literature, Ouahabi et al reported that the Pistacia lentiscus leaf extract possesses β-carotene bleaching activity comparable to the value obtained in our study, with an IC 50 value of 0.19 mg/ml [42]. Our obtained results have shown that the high polyphenol content could probably afect the oxidative power of the extract, which is in accordance with the literature search which indicated that higher antioxidant activity was related directly to the high amount of phenolic compounds [46].…”
Section: Antioxidant Activitysupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, the diferent organs of the plant under study were tested as potential natural antioxidants, where the highest activity was observed in leaf extracts with IC 50 � 0.166 ± 0.001 mg/mL compared to the stems, fruits, and roots with the following values, 0.076 ± 0.001 mg/mL, 0.772 ± 0.043 mg/ml, and 0.370 ± 0.002 mg/mL, respectively [45]. Based on the literature, Ouahabi et al reported that the Pistacia lentiscus leaf extract possesses β-carotene bleaching activity comparable to the value obtained in our study, with an IC 50 value of 0.19 mg/ml [42]. Our obtained results have shown that the high polyphenol content could probably afect the oxidative power of the extract, which is in accordance with the literature search which indicated that higher antioxidant activity was related directly to the high amount of phenolic compounds [46].…”
Section: Antioxidant Activitysupporting
confidence: 79%
“…Also, our fndings are consistent with those reported by Ouahabi et al; this applies to the leaves of Pistacia lentiscus collected in the eastern region of Morocco. It was found that the extract contains many phenolic compounds, such as catechin, quercetin, and p-coumaric acid, along with other notable compounds [42].…”
Section: Qualitative Identifcation Of Chemical Composition Ofmentioning
confidence: 99%
“…However, the medium and high-dosage groups display higher T-AOC levels than the model group ( p > 0.05). The antioxidant prowess of cassia seed fermentation solution can be attributed to its antioxidant constituents, such as polyphenols, known to inhibit free radical activity, thereby mitigating tissue damage and aging ( Salamatullah, 2022 ). This notably elevates the CAT content within zebrafish ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Salamatullah investigated the chemical composition, as well as the antioxidant, anti-inflammatory, and analgesic properties, of a polyphenol-rich fraction from Withania adpressa Coss. ex Batt [9]. High-performance liquid chromatography (HPLC) was applied and revealed bioactive phenols including epicatechin, apigenin, luteolin, quercetin, caffeic acid, p-coumaric acid, and rosmarinic acid.…”
mentioning
confidence: 99%